Facile Synthesis of Hierarchical Nanosized Single‐Crystal Aluminophosphate Molecular Sieves from Highly Homogeneous and Concentrated Precursors. (29th January 2020) - Tao, Shuo; Li, Xiaolei; Wang, Xiaoge; Wei, Ying; Jia, Yunling; Ju, Jing; Cheng, Yuanhui; Wang, Huaisheng; Gong, Shuwen; Yao, Xingjun; Gao, Haixu; Zhang, Cunyin; et al.
Abstract: The synthesis of hierarchical nanosized zeolite materials without growth modifiers and mesoporogens remains a substantial challenge. Herein, we report a general synthetic approach to produce hierarchical nanosized single‐crystal aluminophosphate molecular sieves by preparing highly homogeneous and concentrated precursors and heating at elevated temperatures. Accordingly, aluminophosphate zeotypes of LTA (8‐rings), AEL (10‐rings), AFI (12‐rings), and ‐CLO (20‐rings) topologies, ranging from small to extra‐large pores, were synthesized. These materials show exceptional properties, including small crystallites (30–150 nm), good monodispersity, abundant mesopores, and excellent thermal stability. A time‐dependent study revealed a non‐classical crystallization pathway by particle attachment. This work opens a new avenue for the development of hierarchical nanosized zeolite materials and understanding their crystallization mechanism. Abstract : MfG : AEL‐, AFI‐, LTA‐ und ‐CLO‐Typ‐Aluminophosphat‐Molekularsieb‐Nanokristalle mit intrakristallinen Mesoporen wurden aus hochhomogenen und konzentrierten Vorläufern ohne Wachstumsmodifikatoren oder Mesoporogene synthetisiert.